2017
DOI: 10.1016/s1473-3099(16)30534-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of a nurse-delivered intervention to improve adherence to treatment for HIV: a pragmatic, multicentre, open-label, randomised clinical trial

Abstract: Netherlands Organisation for Health Research and Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…In addition to stressful events, participants reported a wide range of environmental factors which impacted on their ability to adhere. Being able to plan how to overcome these barriers or ‘coping planning’ (Sniehotta et al ., ) is also likely to be an important part of a successful intervention to improve adherence (de Bruin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to stressful events, participants reported a wide range of environmental factors which impacted on their ability to adhere. Being able to plan how to overcome these barriers or ‘coping planning’ (Sniehotta et al ., ) is also likely to be an important part of a successful intervention to improve adherence (de Bruin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Participants across the board reported that, at least on occasion, they struggled to plan to take nebulizers and most highlighted the importance of routines in being able to adhere. Action planning (Sniehotta, Schwarzer, Scholz, & Schüz, ) is therefore likely to be an important component and has been used successfully in interventions to increase adherence to medication in other conditions (de Bruin et al ., ; O'Carroll et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another economic evaluation reached similar conclusions: an 18-month study using electronic medication monitors to improve viral load was also found to be cost-effective with a per person QALY gain only 15% different than the lifetime estimate in this analysis. 62 The study has several strengths and limitations. The strengths include the large study size, the availability of patient-level laboratory data, and the use of two reference cases (societal and health care sector).…”
Section: Discussionmentioning
confidence: 99%
“…Re-engaging OOC patients is considered within the scope of nursing practice and, despite a lack of formal or systematic efforts by nurses in the current model of care, their involvement in re-engagement efforts is likely to be key. Indeed, their clinical experience and knowledge about patients could be helpful in determining how and when patients should be re-engaged into care [13,14].…”
Section: Introductionmentioning
confidence: 99%